Analysis of Various Active Noise Control Algorithms for Cancelling Noise using Matlab - Anubhuti Singh, Vanita Batra, Dr. Sandeep Tayal (International Journal of Advanced Science and Technology, 2020)
In acoustic signal processing, cancellation of noise and noise control are basic complication over a structural region. In last three decade huge work executed on active noise control technology and with time implemented in real time applications to reduce noise for example transportation, audio and many more. Due to massive research work, new technology came into existence and more advance computational microprocessors developed by researchers to get optimum zed output in ANC system. There are various algorithms available to control noise and this paper is incorporation of various algorithms for active noise control. This research work provides an analysis of different adaptive algorithms for noise cancellation. In our research work LMS, NLMS, Fx-LMS, Fu-LMS algorithms implemented and detailed analysis carried out in term of convergence, step size.